2019
DOI: 10.1002/jsfa.9662
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of 11 different plant extracts on the antioxidant capacity of blood and selected tissues in lightweight lambs

Abstract: BACKGROUND: Due to the growing public concern regarding the addition of chemical antioxidants to foods, focus has shifted towards natural alternatives. Because of their antioxidant potential, culinary herbs and spices have long been used to extend the shelf-life of foods. However, a better understanding of the fate of these products following intake is required to assess their use in lamb diets. RESULTS: Two hundred and eighty-eightRasa Aragonesa male lambs (70 days old) were supplemented (5.0 g kg −1 compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 45 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…The research results are consistent with current studies using thyme and other plant extracts. In the study in which 11 different plant extracts, including thyme, were used for lamb feeding, it was reported that the blood antioxidant activity was not affected [37] . Gumus et al [24] reported in their study that the use of oregano oil in the lambs not effected liver SOD values but GSH and CAT values, and also affected GSH, SOD, and CAT enzyme activities in M. longissimus dorsi tissue muscle significantly.…”
Section: Discussionmentioning
confidence: 99%
“…The research results are consistent with current studies using thyme and other plant extracts. In the study in which 11 different plant extracts, including thyme, were used for lamb feeding, it was reported that the blood antioxidant activity was not affected [37] . Gumus et al [24] reported in their study that the use of oregano oil in the lambs not effected liver SOD values but GSH and CAT values, and also affected GSH, SOD, and CAT enzyme activities in M. longissimus dorsi tissue muscle significantly.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that cell or tissue damage is related to free reactive oxygen radicals (ROS; reactive oxygen species) and associated nitrogen degradation products [1][2][3][4][5]. These radicals are high-energy molecules that have free electrons in their outer orbits, and can easily interact with other molecules and cause DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…Various antioxidant compounds are used in medicine to prevent these pathologies [1,2,9,10]. These compositions include various immunological and pharmacological agents, vitamins, fruits, vegetables, food supplements, herbal products, or spices [1,2,4,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosemary has been widely used as a culinary spice and medicinal herb for centuries. Rosemary and rosemary extract (RE) are rich in polyphenolic compounds and show various bioactive properties, such as antioxidant, antibacterial, antidiabetic, anti‐inflammatory, neuroprotective, and hepatoprotective effects . However, the effect of RE on lipid oxidation during gastrointestinal digestion has not been well investigated.…”
Section: Introductionmentioning
confidence: 99%